Terapi Hipnotis Lima Jari Pada Ibu Hamil Dengan Kecemasan Di Kecamatan Kuranji Kota Padang - Diana Arianti; Amelia Susanti (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
COVID-19 outbreaks cause many restrictions on almost all routine services, both access and quality, including restrictions in maternal and neonatal health services, such as a reduction in the frequency of pregnancy examinations and delays in the class of pregnant women (Directorate of Family Health, 2020). The purpose of this activity is so that pregnant women who are in kuranji sub-district of kuranji health center work area kuranji padang city can understand about anxiety and train themselves how to overcome anxiety both during pregnancy and in daily life, so that it is not fatal for pregnancy during this outbreak.Counseling activities were conducted on February 8, 2022 with counseling methods on anxiety and training / training of five-finger hypnotic therapy. The first series of authors provides information about anxiety, causes and ways to cope with pregnancy. Furthermore, one way to overcome anxiety is five-finger hypnosis. Starting with the example by the team do then one-on-one participants do / practice independently.